The income elasticity of culture consumption in Cali (2012)
This article analyzes the consumption of culture in Cali (Colombia), by estimating the income elasticity of cultural demand. The results correspond exclusively to a group of cultural goods and services, unlike previous contributions where calculations have been made for education and culture together. By using the Incomes and Expenditures Survey of 2010, we found that the elasticity of the cultural demand is close to unity (0.99), but different from one at 95% of statistical significance. For this reason, we cannot categorically assert that cultural goods and services are luxury goods.